Effect of 70-kDa and 148-kDa dextran hydrogels on praziquantel solubility - Campos, Flávio Dos Santos [UNESP]; Ferrari, Laís Zuzzi [UNESP]; Cassimiro, Douglas Lopes [UNESP]; Ribeiro, Clóvis Augusto [UNESP]; De Almeida, Adélia Emilia [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (Springer Nature, 2016)
Praziquantel is an anthelmintic widely used in the treatment of schistosomiasis. Although a highly permeable drug, praziquantel is poorly soluble in water, limiting its bioavailability. Improving the solubility of poorly water-soluble drugs has become an important issue for analysis in pharmaceutical research. The use of dextran hydrogels is an advantageous strategy and the focus of extensive research. In this study, several hydrogels were developed from homologous polymer blends using 70 and 148 kDa dextrans in different proportions containing praziquantel, with the aim of evaluating the effects of polymeric release systems on the solubility of poorly water-soluble drugs such as praziquantel. Nine formulations were prepared, and the solubility of the drug incorporated was assessed. Three of the formations were selected to be characterized by DSC for the study in order to gain a better understanding of the thermal behavior of praziquantel incorporated into dextran hydrogels and the influence of polymers on the solubility of the drug, complemented by XRD and SEM techniques. According to the results, formation of crystallites of praziquantel occurred, probably due to the preparation procedures of the formulations, covering the surface of the polymer matrix and promoting a slight improvement in solubility. These data show that the use of hydrogels for the purposes of improving the solubility of poorly water-soluble drugs represents an effective strategy.
Keywords: Dextran; Homologous polymer blend; Hydrogels; Praziquantel; Solubility; Thermal analysis